Analysis of hard protein corona composition on selective iron oxide nanoparticles by MALDI-TOF mass spectrometry: identification and amplification of a hidden mastitis biomarker in milk proteome - Magro, Massimiliano; Zaccarin, Mattia; Miotto, Giovanni; Da Dalt, Laura; Baratella, Davide; Fariselli, Piero; Gabai, Gianfranco; Vianello, Fabio (Analytical and bioanalytical chemistry, 2018)
Surface active maghemite nanoparticles (SAMNs) are able to recognize and bind selected proteins in complex biological systems, forming a hard protein corona. Upon a 5-min incubation in bovine whey from mastitis-affected cows, a significant enrichment of a single peptide characterized by a molecular weight at 4338 Da originated from the proteolysis of aS1-casein was observed. Notably, among the large number of macromolecules in bovine milk, the detection of this specific peptide can hardly be accomplished by conventional analytical techniques. The selective formation of a stable binding between the peptide and SAMNs is due to the stability gained by adsorption-induced surface restructuration of the nanomaterial. We attributed the surface recognition properties of SAMNs to the chelation of iron(III) sites on their surface by sterically compatible carboxylic groups of the peptide. The specific peptide recognition by SAMNs allows its easy determination by MALDI-TOF mass spectrometry, and a threshold value of its normalized peak intensity was identified by a logistic regression approach and suggested for the rapid diagnosis of the pathology. Thus, the present report proposes the analysis of hard protein corona on nanomaterials as a perspective for developing fast analytical procedures for the diagnosis of mastitis in cows. Moreover, the huge simplification of proteome complexity by exploiting the selectivity derived by the peculiar SAMN surface topography, due to the iron(III) distribution pattern, could be of general interest, leading to competitive applications in food science and in biomedicine, allowing the rapid determination of hidden biomarkers by a cutting edge diagnostic strategy. Graphical abstract The topography of iron(III) sites on surface active maghemite nanoparticles (SAMNs) allows the recognition of sterically compatible carboxylic groups on proteins and peptides in complex biological matrixes. The analysis of hard protein corona on SAMNs led to the determination of a biomarker for cow mastitis in milk by MALDI-TOF mass spectrometry.
Keywords: Models, Molecular; Nanoparticles; Whey; Protein Corona; mléčné bílkoviny; Proteomics; Female; Biomarkers; zvířata; molekulární modely; proteomika; proteinová korona; peptidy; Mastitis, Bovine; Peptides; Amino Acid Sequence; Ferric Compounds; Cattle; biologické markery; ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Milk; skot; nanočástice; železité sloučeniny; mastitida skotu; Milk Proteins; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; syrovátka; mléko; sekvence aminokyselin